The global financial cycle and macroeconomic tail risks - Johannes Beutel; Lorenz Emter; Norbert Metiu; Esteban Prieto; Yves Schüler (Deutsche Bundesbank, 2022)
We study the link between the global financial cycle and macroeconomic tail risks using quantile vector autoregressions. Contractionary shocks to financial conditions and monetary policy in the United States cause elevated downside risks to growth around the world. By tightening financial conditions globally, these shocks affect the left tail of the conditional output growth distribution more strongly than the center of the distribution. This effect is particularly pronounced for countries with less flexible exchange rate arrangements, higher foreign currency exposures, and higher levels of private sector leverage, suggesting that exchange rate policies and macroprudential policies can mitigate downside risks to growth.
Keywords: C32; E23; E32; E44; F44; 330; Financial shocks; Monetary policy; Global financial cycle; Growth-at-Risk; International spillovers; Quantile VAR